Artistic research for a production - Winkelhorn, Kathrine; Christoffersen, Erik Exe (Peripeti, 2017)
How does Hotel Pro Forma develop a new production and what does an artistic process look like? Well, first of all it takes 2-4 years to develop and produce a performance. Each project is associated with extensive research in relation to a topic that will be the focal point of the performance.